Anéis quânticos em superfícies não-orientáveis - Souza, José Fernando Oliveira de (2011)
In this work, we explore the link between geometry and physical properties in 2D quantum rings. With focus on the non-orientable mesoscopic structures, we solve the quantum Möbius strip problem, a quantum ring whose lockdown surface is a Möbius strip, and investigate how the physical properties of those structures answer to the geometric variation of this particular configuration. More precisely, we investigate how the adoption of boundary conditions associated to this specific geometric configuration, in particular, can change the general properties of the 2D quantum rings. In addition, we still study the generalized version of the problem, where the Möbius strip has a finite number n of torsions.